Clinicopathologic differences among patients with behavioral variant frontotemporal dementia - Mendez, Mario F. (2007)
OBJECTIVE: To characterize the presenting symptoms and signs of patients clinically diagnosed with behavioral variant frontotemporal dementia (bvFTD) and who had different neuropathologic findings on autopsy. METHODS: This study reviewed all patients entered as clinical bvFTD in the National Alzheimer’s Coordinating Center’s database and who had both clinical and neuropathologic data from 2005 to 2011. Among the 107 patients identified, 95 had unambiguous pathologic findings, including 74 with frontotemporal lobar degeneration (bvFTD-FTLD) and 21 with Alzheimer disease (bvFTD-AD). The patients with bvFTD-FTLD were further subdivided into τ-positive (n = 23) or τ-negative (n = 51) histopathology subgroups. Presenting clinical signs and symptoms were compared between these neuropathologic groups. RESULTS: The patients with bvFTD-FTLD were significantly more likely than patients with bvFTD-AD to have initially predominant personality changes and poor judgment/decision-making. In contrast, patients with bvFTD-AD were more likely than patients with bvFTD-FTLD to have memory difficulty and delusions/hallucinations and agitation. Within the bvFTD-FTLD group, the τ-positive subgroup had more patients with initial behavioral problems and personality change than the τ-negative subgroup, who, in turn, had more patients with initial cognitive impairment and speech problems. CONCLUSION: During life, patients with AD pathology may be misdiagnosed with bvFTD if they have an early age at onset and prominent neuropsychiatric features despite having greater memory difficulties and more intact personality and executive functions than patients with bvFTD-FTLD. Among those with FTLD pathology, patients with τ-positive bvFTD were likely to present with behavior/personality changes. These findings offer clues for antemortem recognition of neuropathologic subtypes of bvFTD.